Les choix de facturation du commerce international : état des lieux, déterminants, inertie de la monnaie - Adrien Faudot (Revue de la Régulation)
Despite the appearance of competition between currencies, the US dollar remains the invoicing currency among the actors of international trade. Such observation is derived from ample statistical evidence contained in this thesis. This observation represents the starting-point of a broader reflection on the rationale underlying the choice of an invoicing currency in international trade, which is the central question which this thesis aims to address. Various determinants have been closely examined by the academic literature to that end. Three approaches dealt with the subject, each with its distinct methodology, and can therefore be analyzed comparatively : the standard macroeconomic approach, the institutionalist approach, and the international political economy approach. The main result of this thesis is that preference for the US dollar cannot be explained exclusively by the instrumental approaches of money which usually prevail in international macroeconomics : their contributions are useful but inadequate as they envision money primarily as a tool for maximizing individual utilities. By applying the institutionalist reading to international exchanges, the thesis introduces the necessity of trust and ethical appeal that money inspires, and the centrality of the social order that its regulatory institutions pursue. This necessity was reasserted throughout the twentieth century, as competing currencies failed to challenge the supremacy of the dollar. It is also evidenced by the resilience of the American currency itself.